The Threat Of Online Sexual Violence And Social Media Pitfalls in Adolescents: Retno Manuhoro Setyowati - Setyowati, Retno Manuhoro (Samudra Publisher, 2023)
This article focuses on adolescents who actively use social media and their vulnerability to Online Gender-Based Violence. The research was conducted qualitatively using the virtual ethnography method to look at the social and cultural phenomena of using cyberspace. As an analytical tool, the author uses Mead's Symbolic Interaction Theory to explore the phenomenon of OGBV among teenagers. The emergence of the phenomenon of online gender-based violence is one of the many negative impacts of using social media. Teenagers who became informants stated that they were afraid of losing their virtual communities on social media and not enough had been literate about online gender-based violence. This research confirms that there is still a need for more digital safety literacy that directly focuses on Online Gender-Based Violence and also needs literacy in pockets of youth and adolescents, accompanied by targeted understanding, so that adolescents can avoid the emergence of OGBV and other negative impacts.